2005
DOI: 10.1007/s00706-005-0392-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Assessment of the Sn–Ti System

Abstract: Summary. The knowledge of phase equilibria and thermodynamic properties in the ternary Cu-Sn-Ti system is of technical importance for active brazing filler metals. Thermodynamic descriptions of the binary systems Cu-Ti and Cu-Sn are well established. In this work a self-consistent thermodynamic description of the Sn-Ti binary system has been obtained by fitting critically reviewed thermochemical and phase diagram data. The newest and most consistent lattice stability has been used, and all the intermetallic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Further studies confirmed the composition of this phase to be Sn 3 Ti 2 . [27,28] Note that at the aging temperature, on the Sn-rich part of the phase diagram, there is a two-phase region where Sn 3 Ti 2 and liquid Sn coexist, in agreement with our observations. [28] The evolution of the diameter of the NiTi fiber and thickness of each interphase gives additional insight into the possible diffusion mechanisms taking place ( Figure 7).…”
Section: A Microstructure Evolution Of Niti In Liquid Snsupporting
confidence: 91%
“…Further studies confirmed the composition of this phase to be Sn 3 Ti 2 . [27,28] Note that at the aging temperature, on the Sn-rich part of the phase diagram, there is a two-phase region where Sn 3 Ti 2 and liquid Sn coexist, in agreement with our observations. [28] The evolution of the diameter of the NiTi fiber and thickness of each interphase gives additional insight into the possible diffusion mechanisms taking place ( Figure 7).…”
Section: A Microstructure Evolution Of Niti In Liquid Snsupporting
confidence: 91%
“…Using the optimised set of Gibbs energies a phase diagram was calculated. The conclusions of Liu et al [23] and Yin et al [24] are that more experiments on thermodynamic properties are required for a better description of the Sn-Ti system. Indeed the only available experimental thermodynamic information concerning the solid phases is the standard enthalpy of formation of the Sn 5 Ti 6 compound which was determined by Meschel and Kleppa [25] by high temperature direct reaction calorimetry (À43.4 AE 1.4 kJ/mol of atoms at 298.15 K).…”
Section: Introductionmentioning
confidence: 96%
“…Two thermodynamic descriptions of the Sn-Ti system were obtained recently by Liu et al [23] and Yin et al [24], by means of the CALPHAD technique using the available experimental data. In the latter work [24] differential thermal analysis measurements were performed at tin-rich side and the results used in the assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Ti-Sn has been systematically studied [7][8][9][10][11][12][13][14]. The version of Ti-Sn system ( Figure 1a) as given by Yin et al was taken because the coordinates of eutectic L Ø (β-Ti) + Ti 3 Sn correspond better to the version of the system presented in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…%, respectively. In addition, Ti 6 Sn 5 has two crystal structures: orthorhombic α-Ti 6 Sn 5 and hexagonal β-Ti 6 Sn 5 , the later one being found when the temperature was higher than 943 K [8,9]. description fitting in some ternary system [16].…”
Section: Introductionmentioning
confidence: 99%